Accounting for Derivatives - TAN, Pearl Hock Neo (Institutional Knowledge at Singapore Management University, 2014)
Financial derivatives have escalated in significance in terms of their volume in global financial markets, widespread use and financial impact on companies and markets. They are akin to a two-edged sword; their use may mitigate or increase risk. Spectacular collapses in the past have brought considerable attention to these instruments. However, when used for hedging purposes, they potentially enhance or preserve value and mitigate risk of financial distress. Accounting for derivative instruments has had a difficult history with accounting standards adopting a piecemeal approach in accounting for financial instruments. However, accounting standards now require derivatives to be recognized on the balance sheet at fair values. Special requirements relating to hedge accounting apply to derivative contracts that are entered into for risk mitigation. The United States were faster in arriving at a comprehensive standard that required companies to report their derivative contracts on the balance sheet. The International Accounting Standards Board (IASB) had a more challenging task to garner support from its member bodies worldwide to adopt the on-balance sheet recognition of derivative contracts. However, its path-breaking standard, IAS 39 has had an impact on the way companies account for financial instruments. In its effort to reform IAS 39, the IASB has issued IFRS 9 which, while simplifying the accounting for financial instruments, continues to require the on-balance sheet recognition of derivative contracts. The “off-balance” sheet treatment of derivative contracts is clearly a thing of the past.